The Impact of DC Earth Fault Current Shape on Tripping of Residual Current Devices - Czapp, S. (Elektronika ir Elektrotechnika, 2008)
Nowadays the manufacturers of electrical appliances introduce electronic components to improve the performance of their products. Many industrial and domestic devices comprise different types of convertors generating DC earth fault current. The shape of that current influences the RCD tripping. In this paper the impact of DC earth fault current shape on RCD residual operating current is presented and results of laboratory tests are discussed. They prove proper tripping of many RCDs even when the DC component in earth fault current is significantly greater than that required in standards. Results of the DC earth fault current transformation by the Ferranti current transformers are also presented. Ill. 8, tabl. 2, bibl. 4 (in English; summaries in English, Russian and Lithuanian).